2011
DOI: 10.1111/j.1556-4029.2010.01654.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ionizing Gamma Radiation on Natural and Synthetic Fibers and Its Implications for the Forensic Examination of Fiber Evidence*

Abstract: Circumstances of criminal activities involving radioactive materials may mean fiber evidence recovered from a crime scene could have been exposed to materials emitting ionizing radiation. The consequences of radiation exposed fibers on the result of the forensic analysis and interpretation is explored. The effect of exposure to 1-1000 kGy radiation doses in natural and synthetic fibers was noticeable using comparative forensic examination methods, such as optical microscopy, microspectrophotometry, and thin-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…Fluorescent intensity from blue and green excitation began to increase at 90 kGy gamma and was strongly increased at 9000 kGy. This observation differs from the results of Colella et al [90], who reported no spectral changes for white cotton (unlike their results for colored fibers) even for doses of 1000 kGy. Fluorescence in the green increased from pale red to red for 90 kGy, becoming much brighter red for 9000 kGy samples.…”
Section: Visual and Microscopic Analysis Of Hair Paper And Fibercontrasting
confidence: 99%
See 3 more Smart Citations
“…Fluorescent intensity from blue and green excitation began to increase at 90 kGy gamma and was strongly increased at 9000 kGy. This observation differs from the results of Colella et al [90], who reported no spectral changes for white cotton (unlike their results for colored fibers) even for doses of 1000 kGy. Fluorescence in the green increased from pale red to red for 90 kGy, becoming much brighter red for 9000 kGy samples.…”
Section: Visual and Microscopic Analysis Of Hair Paper And Fibercontrasting
confidence: 99%
“…Fading, discoloration, and changes in microscopic appearance were reported for synthetic fibers irradiated by gamma >10 kGy and natural fibers >50 kGy [25,89,90]. Forensic examination was deemed feasible, nevertheless [90,91].…”
Section: Potential Effects Of Radiation On Evidence: Fibers and Hairmentioning
confidence: 99%
See 2 more Smart Citations
“…In industry it can be used for sterilization, DNA alteration in plants and structure and properties material modification. Research in using gamma irradiation for textiles concerns the optimization of textile dyeing, reducing the ecological impact and cultural heritage artifacts biological decontamination (Ahmad Bhatti et al, 2012;Bashar et al, 2018;Blouin and Arthur, 1958;Chirila et al, 2018;Colella et al, 2011;Geba et al, 2014;Machnowski et al, 2012;Millington, 2000;Shubhra and Alam, 2011;Takács et al, 2001;Takács et al, 2000).…”
Section: Introductionmentioning
confidence: 99%